Novel 3-fold metal artifact reduction method for CT images. (September 2021) - Desai, Shrinivas. D.
Highlights: Adjacent slices of artifact affected slice exhibits roughly the same anatomical structures. Novel 3-Fold MAR is hybrid approach based on interpolation based sinogram correction method. 3-Fold MAR is performing consistently better as compared to NMAR and LIMAR methods. 3-Fold MAR preserves edge, contrast information and removes original streaking artifacts. 3-Fold MAR method has 75.23% improvement in metal artifact correction as compared to conventional method. Abstract: Metal-induced artifacts are one of the most common streaking artifacts in CT images which are caused by metallic implants within the patient's body. These streaking artifacts are due to attenuation of X-ray photons passing through these objects, resulting in truncated projections, where gaps are formed in projection data. Metal artifacts can corrupt CT images such that they become challenging to read and interpret, eventually leading to limited diagnostic value. In this paper, a novel 3-Fold metal artifact reduction (MAR) method is proposed, where CT slices which are adjacent to artifact affected are used to correct metal artifact affected CT image. It is a hybrid approach involving the sinogram interpolation correction, projection-profile prediction and iterative algebraic reconstruction technique (ART). The proposed MAR method is compared with recently reported iterative frequency split–normalized (IFS) and L0 – Douglas-Rachford splitting (L0 -DRS) MAR approaches using clinical cases of hip prostheses, maintaining the similar experimental environment. Performance comparison by means of 'reference free ground truth' metric revealed greater ability and acceptability of proposed methods. 3-Fold MAR method emerged as most promising technique, with excellent quantitative and qualitative score.